Perlindungan Hukum Terhadap Hak Cipta Aplikasi Spotify Atas Pencantuman Fitur Spotify Codes Secara Komersial - Finna Noor Eka Ayu; Deny Slamet Pribadi; Lily Triyana (Jurnal Risalah Hukum, 2022)
The sophistication of features in the Spotify application, namely Spotify Codes, is exploited by business actors by including them on products that are traded without the permission of the creator and/or copyright holder of the application. This act has violated the application's copyright, namely its economic rights. In addition, commercial inclusion or obtaining profits also causes losses in terms of economic rights to the creator and/or copyright holder of the Spotify application. This study uses a doctrinal research approach based on literature by analyzing primary legal materials and secondary legal materials. The results obtained from this study can be concluded that the legal protection of the copyright of the Spotify application in the form of preventive and repressive legal protection is contained in Law Number 28 of 2014 concerning Copyright. Furthermore, the form of civil liability for the commercial inclusion of the Spotify Codes feature is compensation for any unlawful act in accordance with the provisions of Article 1365 of the Civil Code in the form of copyright infringement. However, the application of legal protection and civil liability has not been maximized due to the nature of the complaint, so it requires a complaint from the creator or copyright holder of the Spotify application to be followed up.